Teachers' Perceptions of the Development of Integrated Social Studies Student Worksheets Based on Social and Religious Values in Elementary Schools - Eka Yusnaldi; Pangulu Abdul Karim (MASI Mandiri Edukasi, 2025)
This study aims to explore teachers’ perceptions of the development of Integrated Social Studies (IPS) Student Worksheets (LKPD) based on social and religious values in State Elementary School 152979 Pandan 1. The study is grounded in the importance of integrating character values into Social Studies learning to support the formation of the Pancasila Student Profile. A descriptive qualitative approach was employed, supported by quantitative data from a four-point Likert-scale questionnaire, in-depth interviews, and a document review of the LKPD. The research subjects were 10 teachers involved in Social Studies instruction. The questionnaire instrument comprised four dimensions: the urgency and benefits of value-based LKPD, ease of development and implementation, availability of support, and impact on students’ attitudes, interests, and social interactions. The findings revealed that the “impact on students” dimension scored the highest (3.90), followed by “urgency and benefits” (3.85), “ease of development and implementation” (3.10), and “availability of support” (2.75). Teachers believe that value-based LKPD is effective in improving students’ learning motivation, social skills, and positive attitudes, although technical constraints and limited institutional support remain challenges. The study recommends continuous training, provision of relevant references, and strengthening teacher collaboration to ensure the sustainability of value-based LKPD implementation in elementary schools.